2021
DOI: 10.3233/jhd-200438
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mismatch Repair and its Role in Huntington’s Disease

Abstract: DNA mismatch repair (MMR) is a highly conserved genome stabilizing pathway that corrects DNA replication errors, limits chromosomal rearrangements, and mediates the cellular response to many types of DNA damage. Counterintuitively, MMR is also involved in the generation of mutations, as evidenced by its role in causing somatic triplet repeat expansion in Huntington’s disease (HD) and other neurodegenerative disorders. In this review, we discuss the current state of mechanistic knowledge of MMR and review the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 225 publications
(349 reference statements)
3
62
0
Order By: Relevance
“…The MMR pathway is best characterized for its role in correcting DNA mismatches generated during DNA replication but has additional functions in DNA recombination and in DNA damage signaling (reviewed in [47,151,152]). In mammals, MSH2-MSH6 dimers (MutS␣) primarily recognize base-base mismatches, whereas MSH2-MSH3 dimers (MutS␤) primarily recognize insertion-deletion loops.…”
Section: Mismatch Repair Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMR pathway is best characterized for its role in correcting DNA mismatches generated during DNA replication but has additional functions in DNA recombination and in DNA damage signaling (reviewed in [47,151,152]). In mammals, MSH2-MSH6 dimers (MutS␣) primarily recognize base-base mismatches, whereas MSH2-MSH3 dimers (MutS␤) primarily recognize insertion-deletion loops.…”
Section: Mismatch Repair Factorsmentioning
confidence: 99%
“…For the purpose of this review, we use the term "DNA repair" to describe the process or function to which genes or pathways are traditionally assigned, rather than the functional outcome of that process in the context of expanded repeats. More specifically, and as an example, we use the term "mismatch repair" (MMR) to mean the canonical post-replicative pathway and its components [47], acknowledging that the specific functions of the proteins in the pathway may be different in the context of expanded repeats.…”
Section: Introductionmentioning
confidence: 99%
“…Swami et al [14] investigated somatic expansion in post-mortem DNA samples from HD patients, and showed that patients with particularly early-onset have a higher proportion of large expansions in the cortex. Most recently, genetic association studies in HD patient cohorts have revealed the association between DNA repair gene variants and age at motor signs of HD and HD progression [15][16][17][18][19]. These data suggest that somatic CAG repeat expansions contribute toward HD pathology.…”
Section: Introductionmentioning
confidence: 97%
“…Another clear prediction of the DNA replication slippage model is that loss of function mutations in the postreplicative DNA mismatch repair pathway should increase the frequency of expansions. This prediction was turned on its head in 1999, when Manley et al demonstrated that the complete reverse was true and that the obligate mammalian MutS homologue Msh2 was absolutely required to generate somatic expansions [232] (see Iyer and Pluciennik, this issue, for more details on the DNA mismatch repair pathway [233]). These insights were extended when it was shown that Msh3, but not Msh6, was also essential for the somatic expansion of CAG•CTG repeat expansions, directly implicating the MSH2/MSH3 MutSBeta complex [234].…”
Section: The Drivers Of Instability: Somatic Expansion Is Cell-divisimentioning
confidence: 99%
“…Cell division-independent inappropriate DNA mismatch repair has thus come to the fore as a likely mechanism of expansion of CAG•CTG repeats [238]. Along with other in vitro experiments, these animal model studies were critical in establishing the key players in the expansion pathway (for more details, see Wheeler and Dion, and Iyer and Pluciennik, in this issue [169,233]). However, in most cases, these studies did not lead directly to insights into the accrual of somatic expansions in mediating pathology (although see below).…”
Section: The Drivers Of Instability: Somatic Expansion Is Cell-divisimentioning
confidence: 99%